Facile synthesis of ZnS-ZnO nanocomposites for enhanced photocatalytic activity. (23rd February 2017) - Ma, Qun; Wang, Zhengshu; Jia, Hanxiang; Wang, Yongqian
Abstract : Novel ZnS–ZnO nanocomposites were successfully synthesised via a facile thermal treatment of ZnS microstructure spheres. Microstructure, morphological and photocatalytic activity were fully investigated. X-ray diffraction patterns indicated that the ZnO was successfully decorated on the surface of ZnS. The microstructure of ZnS was transformed into nanocomposites after the formation of ZnO. The value of band gap decreased from 3.37 to 3.00 eV, which enhanced the light utilise efficiency. The ZnS–ZnO nanocomposites exhibited enhanced photocatalytic activity, compared with pristine ZnS. The enhancement of photocatalytic performance was attributed to the increased light absorption and effective separation of photogenerated electrons–holes.